Body condition, sex and elevation in relation to mite parasitism in a high mountain gecko. (25th November 2019) - Comas, M.
Abstract: Parasitism is one of the main selective forces in nature, strongly affecting host fitness. Still, knowledge is incomplete concerning how variation in probability and intensity of infestation depends on body condition, sex or geographic variables. Here, I study the variation in probability and intensity of infestation of bloodsucking mites parasitizing the Atlas day gecko ( Quedenfeldtia trachyblepharus ) depending on host body condition, sex and elevation, in the High Atlas (Morocco). Parasite prevalence was 58.75%, and probability of infection decreased with host body condition. However, parasitism intensity tended to increase with body condition. The parasite load ranged from 0 to 16 mites per individual, with a mean intensity of 3.0 ± 0.37 (se ) in infested geckos. Prevalence was higher in males (2/3 parasitized) than in females (1/2 parasitized), but intensity did not significantly differ with sex. Neither prevalence nor intensity varied with elevation. In conclusion, geckos in better body condition harboured heavier parasite loads, but animals with the highest body condition were not infested. These findings suggest that animals with good body condition may tolerate heavier mite infestations, but only animals with the highest body condition may resist infestation. Abstract : Here, I show that parasite intensity and probability of infection of bloodsucking mites parasitizing the Atlas day gecko ( Quedenfeldtia trachyblepharus ) did not vary with elevation in the High Atlas (Morocco). Probability of infection decreased with host body condition, but parasitism intensity tended to increase with body condition. Meanwhile, prevalence was higher in males than in females, but intensity did not significantly differ with sex.